Effects of bedding materials on vermicasting potential of red wiggler worms- Eisenia fetida / Assoc. Prof. Hajah Wan Hanisah Wan Ismail … [et al.] - Wan Ismail, Wan Hanisah (Assoc. Prof. Hajah); Ali, Khafiruddin (Haji); Mohd Sahal, Mohd Saiful Akbar; Mamat, Nordin (2006)
Experiments were performed to determine the composting potential of Eisenia fetida over a period of 70 days under laboratory conditions using different substrates as bedding materials. The study indicates that oil palm leaves, acacia leaves, newspaper and sawdust shows different potentials as bedding materials for vermicomposting. However, proper initial preparation of the bedding material is critical to ensure efficient vermicomposting where precomposting of agricultural wastes is needed to facilitate efficient vermicomposting. The study also indicates that particle size of the bedding material affects the rate of vermicomposting. For household vermicomposting, newspaper is recommended as the bedding material because it is cheap, clean or less messy and very easy to handle. Thus study has shown that kitchen wastes' such as left over vegetables and similar wastes can be composted with earthworms and can be converted as valuable garden fertilizer without additional cost.